Conservation of molecular interactions stabilizing bovine and mouse rhodopsin - Kawamura, Shiho (2010)
Rhodopsin is the light receptor that initiates phototransduction in rod photoreceptor cells. The structure and function of rhodopsin is tightly linked to molecular interactions that stabilize and determine the receptor's functional state. Single-molecule force spectroscopy (SMFS) was used to localize and quantify molecular interactions that structurally stabilize bovine and mouse rhodopsin from native disc membranes of rod photoreceptor cells. The mechanical unfolding of bovine and mouse rhodopsin revealed nine major unfolding intermediates, each intermediate defining a structurally stable segment in the receptor. These stable structural segments had similar localization and occurrence in both bovine and mouse samples. For each structural segment, parameters describing their unfolding energy barrier were determined by dynamic SMFS. No major differences were observed between bovine and mouse rhodopsin thereby implying that the structures of both rhodopsins are largely stabilized by similar molecular interactions.